2018
DOI: 10.1177/0891243218787757
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sexual Practice in Structural Context: Condom Use among Women Doing Sex Work in Southern India

Abstract: condom use among Women doing sex Work in southern india Gay younG american university, uSa Mona j. E. DannEr old Dominion university, uSa Lucía fort Independent Gender & Development consultant, uSa KIM M. BLanKEnShIp american university, uSa In this study, we elaborate connections among gender, structure, and practice to suggest how social structural relations shape social sexual practice and, in the process, reshape gender relations. using survey data from a study of a community mobilization intervention, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 52 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…It is these views that perpetuate stigma and the de-humanisation of women in sex work. Research with women involved in sex work in Southern Indiawhere the culture is male dominated, have demonstrated that men"s power over women, including intimate partner violence, makes FSWs more vulnerable to HIV, stating that interventions challenging normative gender relations are imperative in improving the health of FSWs (Young et al 2018). The act of purposefully putting holes in condoms in order to infect or put FSWs at risk of diseases suggests some kind of punishment delivered by the client upon the sex worker (and/or women generally) and is an example of the dangerous attitudes expressed by some clients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is these views that perpetuate stigma and the de-humanisation of women in sex work. Research with women involved in sex work in Southern Indiawhere the culture is male dominated, have demonstrated that men"s power over women, including intimate partner violence, makes FSWs more vulnerable to HIV, stating that interventions challenging normative gender relations are imperative in improving the health of FSWs (Young et al 2018). The act of purposefully putting holes in condoms in order to infect or put FSWs at risk of diseases suggests some kind of punishment delivered by the client upon the sex worker (and/or women generally) and is an example of the dangerous attitudes expressed by some clients.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the incidence of these types of violations the de-criminalization and de-stigmatization of sex work is suggested as a vehicle for changing chauvinistic constructions of women"s sexuality and making society more open to sex work and FSWs (Comte, 2013). Some women, in urban India for example choose to do sex work, as their options in regards to making a livelihood are relatively limited (Young et al 2018). The sex trade in India has been defined as a crucial part of the interconnected array of livelihood strategies that low SES women pursue for survival (Young et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations